2020
DOI: 10.5432/ijshs.202023
|View full text |Cite
|
Sign up to set email alerts
|

Conditions and Hardships Related to Pharmacists' Provisions of Anti-Doping Activities in Japan

Abstract: We conducted a cross-sectional survey of pharmacists working in hospitals and community pharmacies in Japan to assess anti-doping activities, aiming to improve athletes' medication support. An internet survey was conducted anonymously using a structured questionnaire, with items regarding the respondent's basic information, their collaboration with other healthcare professionals, and their experiences with medication support for athletes. Of the 841 pharmacists who completed the survey, 21.4% had experienced a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 13 publications
(16 reference statements)
0
1
0
Order By: Relevance
“…Nakajima et al reported that 45.0% of sports pharmacists responded with "I know the procedures for dealing with doping inquiries, but I cannot respond with confidence." 7) Lack of experience and absence of information sharing among sports pharmacists might lead to a lack of confidence in handling doping inquiries. Establishing a network among sports pharmacists should be considered.…”
Section: Activities and Challengesmentioning
confidence: 99%
“…Nakajima et al reported that 45.0% of sports pharmacists responded with "I know the procedures for dealing with doping inquiries, but I cannot respond with confidence." 7) Lack of experience and absence of information sharing among sports pharmacists might lead to a lack of confidence in handling doping inquiries. Establishing a network among sports pharmacists should be considered.…”
Section: Activities and Challengesmentioning
confidence: 99%
“…The evidence points to General Practitioners as an essential asset to anti-doping regulation agencies which they need to optimize to curtail doping. The practitioners can play a core part in educating athletes about the danger of PEDs and cut off the link as a source of doping substances (Nakajima et al, 2020). A study involving medical doctors from Iraq reported that 37.5% (24) participants had interacted with athletes with a history of doping (Salih & Abd, 2021).…”
Section: Introductionmentioning
confidence: 99%